2021
DOI: 10.1111/gcbb.12825
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life cycle assessment of bio‐based insulation materials: Environmental and economic performances

Abstract: Insulation materials decrease the final energy consumption of buildings. In Germany, fossil and mineral insulations dominate the market despite numerous life cycle assessments (LCAs) showing that bio‐based insulations can offer environmental benefits. Evaluating the results of such LCAs is, however, complex due to a lack of comparability or costs considered. The objective of this study is comparing bio‐based insulations under equal conditions to identify the most environmentally friendly and cost‐efficient mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Meeting the same function among non-wood and woodbased products often requires varying mass amounts of each. For construction materials, this can result in substantially different mass replacement ratios (in the following also called replacement rates) (Cordier et al 2021), e.g., depending on the building type (Peñaloza et al 2019), or physical properties such as density or the thermal conductivity (Schulte et al 2021a). Given the variety of construction materials covered in this study, mass replacement rates according to multiple materials were adapted from Peñaloza et al (2016), Mehr et al (2018), and Piccardo and Gustavsson (2021) (Supplementary Material).…”
Section: Substitution Effectsmentioning
confidence: 99%
“…Meeting the same function among non-wood and woodbased products often requires varying mass amounts of each. For construction materials, this can result in substantially different mass replacement ratios (in the following also called replacement rates) (Cordier et al 2021), e.g., depending on the building type (Peñaloza et al 2019), or physical properties such as density or the thermal conductivity (Schulte et al 2021a). Given the variety of construction materials covered in this study, mass replacement rates according to multiple materials were adapted from Peñaloza et al (2016), Mehr et al (2018), and Piccardo and Gustavsson (2021) (Supplementary Material).…”
Section: Substitution Effectsmentioning
confidence: 99%
“…Moreover, the economic viability of hemp fibers for various applications depends on the cost‐effective acquisition of fiber material, influenced by fluctuations in the fiber process (Seile et al., 2022). In fact, high cultivation (particularly N fertilization) and manufacturing costs has led to relative cost inefficiencies at the upstream level as compared to alternative bio‐based solutions such as miscanthus (Schulte et al., 2021). From the producer's perspective, high input costs may infer low relative profitability, regardless of the ultimate use.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the replacement of the marginal electricity mix (Vandepaer et al, 2019) would reduce the reported avoided burden by over 50%, because the anticipated marginal electricity in 2030 relies to only 25% on fossil fuels. The potential substitution effects of other miscanthus products were not considered; however, available LCA studies for material use show benefits in the impact category climate change (Ntimugura et al, 2021; Patel et al, 2018; Schulte et al, 2021; Wagner et al, 2017). Nevertheless, assuming the absence of a substitution effect, the GHG balance for all scenarios would still be lower than the reference, because the carbon sequestration alone outweighs the additional emissions from iLUC.…”
Section: Discussionmentioning
confidence: 99%